Checklist of oribatid mites (Acari: Oribatida) of Canada and Alaska - Behan-Pelletier, Valerie M.; Lindo, Zoë (Zootaxa, 2019)
This checklist of the oribatid fauna of Canada and Alaska (excluding Astigmata) includes 580 identified species in 249 genera and 96 families. The known fauna of Canada includes 556 identified species in 247 genera, and that of Alaska includes 182 species in 95 genera; 39 of the 42 oribatid superfamilies are represented. We further list 300 species that are currently unidentified, and possibly undescribed. In addition, we list 42 genera that are represented only by unidentified and probably undescribed species. For each species we give combinations and synonymies, specific locations in Alaska and the Provinces and Territories of Canada, habitats, and biogeography. There are 182 identified species known for Alaska, 152 for Yukon, 122 for Northwest Territories, 58 for Nunavut; 210 for British Columbia, 213 for Alberta, 15 for Saskatchewan, 84 for Manitoba, 167 for Ontario, 210 for Québec, 110 for Nova Scotia, 77 for New Brunswick, 84 for Newfoundland and 6 for Prince Edward Island. The known fauna of Canada is smaller than that of Austria, and is approximately equivalent to that of the Czech Republic. As these countries are much smaller in size than Canada and less ecologically diverse, we consider the Canadian and Alaskan fauna are at most 25% known. The paucity of these data reflects the absence of taxonomic and faunistic studies on Oribatida in State, Provinces or Territories, and especially in the Canadian and Alaskan National Park systems and the hundreds of Provincial Parks. Despite the almost 90% increase in described species since the catalogue of Marshall et al. (1987), there is a need for focussed, coordinated research on Oribatida in the natural regions throughout Canada and Alaska, and for monographs on families and genera with large numbers of undescribed species, such as Brachychthoniidae, Damaeidae, Cepheidae, Liacaridae, Oppiidae, Suctobelbidae, Hydrozetidae, Phenopelopidae, Scheloribatidae, Haplozetidae and Galumnidae.